Effective interleukin-6 inhibition in a pediatric patient with mevalonate kinase deficiency and chronic nonbacterial osteomyelitis–like bone lesions under interleukin-1 blockade - Tunce, Eray; Atamyıldız Uçar, Sıla; Taşar, Sevinç; Eser, Metin; Sözeri, Betül (The Turkish Journal of Pediatrics, 2026)
Background. Mevalonate kinase deficiency (MKD) is a rare autosomal recessive autoinflammatory disease. Chronic nonbacterial osteomyelitis (CNO) represents another autoinflammatory disorder characterized by sterile bone inflammation. Although musculoskeletal pain is common in MKD, CNO-like bone lesions have rarely been described. Tocilizumab has been used separately in MKD / hyper-IgD syndrome (HIDS) and in CNO; however, pediatric cases showing both conditions together and responding completely to IL-6 blockade have not been previously reported.Case Presentation. We present a 16-year-old boy born to consanguineous parents who experienced early-onset recurrent fever episodes with abdominal pain, maculopapular rash, oral ulcers, and conjunctival injection. He was initially misdiagnosed with FMF and IgA vasculitis and treated with colchicine with partial improvement. Persistent systemic inflammation prompted referral to our tertiary center at age 9. A periodic fever gene panel revealed a homozygous MVK p.V377I mutation, confirming MKD.Anakinra therapy was initiated. Although no attacks occurred during the first month, flares characterized by fever, abdominal pain, rash, and elevated acute-phase reactants recurred in the second and third months, reflecting a partial response. Consequently, treatment was switched to canakinumab. Toward the end of the second year of IL-1 blockade, attack frequency increased to once every three months, and at age 12 he developed diffuse musculoskeletal pain. Whole-body magnetic resonance imaging demonstrated multifocal metaphyseal bone marrow edema compatible with CNO-like lesions. Sulfasalazine was added but discontinued after drug-induced pancreatitis. Given persistent systemic inflammation and inadequate response to IL-1 inhibitors, canakinumab was replaced with weekly subcutaneous tocilizumab, resulting in rapid improvement in bone pain and systemic inflammation. Since the third month of tocilizumab therapy, he has remained clinically stable with normalized inflammatory markers and only a single mild flare over the last year.Conclusion. This case highlights the potential role of IL-6 inhibition in complicated MKD presenting with autoinflammatory bone disease refractory to standard therapies.
Keywords: mevalonate kinase deficiency; hyper-IgD syndrome; chronic nonbacterial osteomyelitis; autoinflammatory bone disease; tocilizumab